Answer:
p=19
Step-by-step explanation:
since the instructions say that ([tex]x^{13}[/tex])([tex]x^{6}[/tex]) is equivalent to [tex]x^{p}[/tex], we can make the equation:
([tex]x^{13}[/tex])([tex]x^{6}[/tex])=[tex]x^{p}[/tex]
now, apply the laws of exponents; [tex]a^{m} * a^{n} =a^{m+n}[/tex]
in that case, since we're multiplying x to the 13th power by x to the 6th, the result is [tex]x^{13+6}[/tex], which is [tex]x^{19}[/tex]
the equation now:
[tex]x^{19}[/tex]=[tex]x^{p}[/tex]
since the exponents are at the same base, we can solve the equation
19=p
so p is 19
hope this helps :)